Locusts of the Year 2000 - 2 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Locusts of the Year 2000 'The fact that there have been no mass invasions of desert or migratory locusts for twenty years does not mean that the threat is over', we were warned in the cover article on the subject in the very first issue of Spore....